ON OD-CHARACTERIZABILITY OF A CERTAIN ALTERNATING AND SYMMETRIC GROUP - Mahmiani, A.; Darafsheh, M.R. (Italian Journal of Pure and Applied Mathematics, 2014)
In this paper we will show that if G is a finite group with the same order and degree pattern as the alternating group on 27 letters, then G is isomorphic to A27. Furthermore we will show that there are three non-isomorphic finite groups with the same order and degree pattern as the symmetric group on 27 letters.